A Brief Description of Different Types of Cancers and Role of Some Herbs & Bioactive Compounds in Lung Cancer Management - Kumar, Roshan; Sood, Prachi; Shaik, Rahaman; Singh, Harjeet Kumar; Verma, Ayush (Journal for Research in Applied Sciences and Biotechnology, 2023)
Cancer immunotherapy has considerably raised patient survival rates and significantly improved patients' quality of life in comparison to the gold standard of care, which includes chemotherapy, radiation therapy, and surgery. Immunotherapy has firmly established itself as a novel pillar of cancer care across the board, from the metastatic stage all the way through adjuvant and neoadjuvant treatment in a wide variety of cancer types. In this overview, the primary emphasis will be placed on the seminal moments in the history of cancer immunotherapy that prepared the way for the cutting-edge treatments that are available today. Cancer treatment that makes use of medicinal herbs and the phytocompounds that can be obtained from those herbs is becoming an increasingly attractive option. It has been demonstrated in a number of clinical studies that the use of herbal medicines in conjunction with conventional therapy can increase survival rates, immunological modulation, and quality of life (QOL) in patients who have cancer. In addition to this, we highlight the challenges and restrictions currently faced by cancer checkpoint immunotherapy as well as the cutting-edge research being conducted in the fields of individualized cancer vaccines, autoimmunity, the microbiome, the microenvironment of tumors, and metabolomics to find solutions to these problems. For hundreds of years, practitioners of traditional medicine have depended on treatments derived from plants. Many studies on their use have been carried out all over the world, and some of the findings have led to the development of medicines that are derived from plants. The global market for medicinal plant products is estimated to be worth more than one hundred billion dollars each year. This research investigates the role, contributions, and utility of medicinal plants in the context of the current strategic methods to disease prevention, notably lung cancer, which is a public health concern. The focus of this research is on the current strategic approaches to disease prevention.